4y-2+3=-2y-4

Simple and best practice solution for 4y-2+3=-2y-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4y-2+3=-2y-4 equation:


4y-2+3=-2y-4

We simplify the equation to the form, which is simple to understand
4y-2+3=-2y-4

We move all terms containing y to the left and all other terms to the right.
+4y+2y=-4+2-3

We simplify left and right side of the equation.
+6y=-5

We divide both sides of the equation by 6 to get y.
y=-0.833333333333

See similar equations:

| -4(7n-4)+4n= | | 11-(7a-a)+11a=4(3a+7) | | 20(31)= | | 8x-11y=32 | | 2y+5x=6 | | x+494=2753 | | 3(8n-2)-3(1-n)+8=8 | | 2x+2j=1-yj | | 5[x-4(4x-5)]=3-2x | | 3y+7=16 | | (2-4j)x+9+(1+4j)=0 | | -3n-2+6n=7n+26 | | 2.97=x+1.6 | | r+.07r=506 | | -3(2y+4)= | | -25x^2+1=0 | | y-4.7=12.52 | | (6c-7d)-(3c+6cd)= | | 2p^2=-4p+1 | | -4x+2=-6 | | 42x-12x^2=0 | | 5x+11=2(4x+7) | | 3s-(0.5s+7.2)=32.8 | | 40y-40=-40+40 | | M=j-k | | -7-(-3-2g)-10=0 | | 7-5x=27 | | b^4=48 | | 4x+4(x+9)=20 | | y^2-10y+2x+25=0 | | (5a^3+6a)+(-3a^2-5a)= | | 2m-14=6 |

Equations solver categories